2021
DOI: 10.3390/su13116260
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agri-Food Systems: Environment, Economy, Society, and Policy

Abstract: Agri-food systems (AFS) have been central in the debate on sustainable development. Despite this growing interest in AFS, comprehensive analyses of the scholarly literature are hard to find. Therefore, the present systematic review delineated the contours of this growing research strand and analyzed how it relates to sustainability. A search performed on the Web of Science in January 2020 yielded 1389 documents, and 1289 were selected and underwent bibliometric and topical analyses. The topical analysis was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 1,240 publications
(395 reference statements)
0
31
0
Order By: Relevance
“…The global COVID-19 pandemic is a stressful situation that has impacted the lifestyles and behaviors of the population suddenly and dramatically and will continue to have a broad direct and indirect influence [3]. Aside from the necessary enhanced focus on human health, concerns emerge about the pandemic's effect on food systems [4,5]. The COVID-19 pandemic and associated containment measures, including mobility restrictions, social distancing, and lockdowns, significantly prejudiced diet, daily food patterns, and general functioning of food systems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The global COVID-19 pandemic is a stressful situation that has impacted the lifestyles and behaviors of the population suddenly and dramatically and will continue to have a broad direct and indirect influence [3]. Aside from the necessary enhanced focus on human health, concerns emerge about the pandemic's effect on food systems [4,5]. The COVID-19 pandemic and associated containment measures, including mobility restrictions, social distancing, and lockdowns, significantly prejudiced diet, daily food patterns, and general functioning of food systems [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, there has been limited systematic research on the sustainability aspects of this topic. A recent bibliographic analysis of publications showed an increasing interest in sustainable food systems and revealed that publications in the field of policy and government on sustainable agri-food systems are overlooked [65] (pp. [13][14].…”
Section: Relationship With Sustainabilitymentioning
confidence: 99%
“…Due to permanent change, the concepts must be constantly modified and adjusted. The impact of the SARS-CoV-2 pandemic has uniquely exemplified the challenges of QM, the risks to FSCs, and the consequences for global food systems [65,[90][91][92][93][94]. For sustainable education and training, the concept of lifelong learning and capacity building should be the focus [95][96][97].…”
Section: Survey Respondentsmentioning
confidence: 99%
“…While these efforts have been critical, many voices have pointed out their worrying psychological, social, and economic effects on global production and consumption systems (2). In the same line of rationale, COVID-19 has impacted agro-food systems at many levels, from farm to fork (3)(4)(5)(6)(7)(8). Indeed, the pandemic had several impacts on diet and food behavior.…”
Section: Introductionmentioning
confidence: 99%